SISTEM MANAJEMEN PEMANTAUAN KEBUTUHAN GIZI ANAK DALAM MASA PERTUMBUHAN DI DESA KARANGJAYA - Budiman, Indra Adi; Chaniago, Herman; Abidin, Dindin; Azhari, Adli; Ridha Kusuma, Rizki (LPPM Universitas Islam 45 Bekasi, 2024)
Karangjaya Village is a rural village where people work in agriculture or small businesses. The majority of the population lives below the poverty line, and access to health services and nutritious food is limited. As a result, child health is a major concern in Karangjaya Village with high rates of malnutrition and stunting in children under five years old. The aim of the community service is to help support an effective and efficient nutrition monitoring programme, so as to help reduce malnutrition and better manage children's health. The method of implementing the service applies counselling in the form of organising seminars for 20 mothers in Karangjaya Village. The results showed an increase in community knowledge about healthy eating patterns, which is expected to reduce the number of malnutrition in Karangjaya Village. Monitoring and evaluation showed positive results, with some children showing improved nutritional status after receiving appropriate treatment. Thus, the nutrition management system in Karangjaya Village contributes significantly to improving children's health and nutrition.